Aesthetics of betrayal. Desire and censorship of gay memory in contemporary art (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2025)
This article offers a critical and controversial analysis of gay history through contemporary art, adopting a negative queer perspective that destabilizes normative narratives of identity, desire, and memory. Through the study of works by artists such as Collier Schorr, Attila Richard Lukacs, Catherine Opie, and Pierre et Gilles, the article explores how visual art can reconfigure traditional representations of homosexual masculinity, particularly those linked to fascist aesthetics, militarism, and fetishism. These artists employ aesthetic ambiguity—between desire and discomfort—to push the boundaries between eroticism, symbolic violence, and politics. The investigation draws upon theoretical frameworks developed by Jack Halberstam, Leo Bersani, and Susan Sontag, whose ideas on masochism, queer negativity, and aesthetic fascination allow these images to be read not as affirmations of identity, but as symbolic acts of betrayal that open new paths for rethinking discomfort.
Keywords: Gay; history; queer; Holocaust; violence